The Effect of Giving Effective Microorganism-4 Probiotics Through Drinking Water on Internal Organs Of Male Bali Ducks - N. M. A. W., Dewi; Siti, N W.; Sukmawati, N. M. S. (Jurnal Peternakan Tropika; Vol 7 No 2 (2019), 2019)
The study aimed to determine the effect of probiotic effective microorganism-4 given through drinking water on the weight of organs of bali male ducks. The research was conducted in a cage belonging to Mr. I Ketut Sunatra located in Kediri, Tabanan for 8 weeks. The design used is a Rancangan Acak Lengkap (RAL) Completely Randomized Design (CRD) consisting of 3 treatments and 5 replications so that there are 15 experimental units, each unit uses 3 Bali male ducks with a body weight of 55.72 ± 7.16 g. The three treatments is drinking water without probiotics Effective Microorganism-4 as the control (P0) , addition of probiotic Effective Microorganism-4 by 0.5% (P1), and the addition of probiotics Effective Microorganism-4 by 1% (P2). The variables observed were the weight of the heart, liver, proventriculus, ventriculus, bile, kidney, small intestine and the length of the small intestine. The results showed that in general the weight of the organs in ducks given the Effective Microorganism-4 probiotics tended to be higher compared to the controls as the level given increased, but statistically not significantly different (P> 0.05). Based on the results of the study it can be concluded that the given of Effective Microorganism-4 probiotics at the level of 0.5% and 1% did not affect the weight of internal organs (weight of heart, liver, proventriculus, ventriculus, bile, kidney, small intestine and length of small intestine) male bali ducks aged 8 weeks.   Key words : male bali duck, internal organs, probiotics